Reversible Watermarking Dengan Kemampuan Koreksi Error - Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2010)
Reversible watermarking with histogram shift on difference image produce thin distortion of image and large capacity. This research adds error correction capability in Lees method. Experimental results demonstrate that the average PSNR value > 49 dB. Watermarked image with 100 x 100 pixel salt n pepper noise on the density of 0.05 is obtained that the watermark with ECC is more robust than a watermark without ECC. JPEG compression in lossless mode may be applied to the watermarked image.Keyword: difference image, histogram, reversible watermarking